2021
DOI: 10.1101/2021.06.10.447906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovering single-cell eQTLs from scRNA-seq data only

Abstract: eQTL studies are essential for understanding genomic regulation. Effects of genetic variations on gene regulation are cell-type-specific and cellular-context-related, so studying eQTLs at a single-cell level is crucial. The ideal solution is to use both mutation and expression data from the same cells. However, current technology of such paired data in single cells is still immature. We present a new method, eQTLsingle, to discover eQTLs only with single cell RNA-seq (scRNA-seq) data, without genomic data. It … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Transferring knowledge studied from in vitro cancer cell lines to single-cell and clinical data tends to be an important direction [14]. However, it is unreliable to call SNVs from clinical and single-cell tumor data covering all candidate loci [17][18][19]. In addition, recent evidence shows that whole tumors collectively act on drugs [12].…”
Section: Assessment Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transferring knowledge studied from in vitro cancer cell lines to single-cell and clinical data tends to be an important direction [14]. However, it is unreliable to call SNVs from clinical and single-cell tumor data covering all candidate loci [17][18][19]. In addition, recent evidence shows that whole tumors collectively act on drugs [12].…”
Section: Assessment Of Methodsmentioning
confidence: 99%
“…Similarly, detecting reliable SNVs covering all hotspots simultaneously from single-cell data is unattainable. Both sequencing coverage and sequencing depth in single-cell data are too low to detect SNVs completely from the data [18,19]. Second, current methods encode gene features as separate units.…”
mentioning
confidence: 99%
“…Most of the studies thus far have used the 10× Genomics Chromium platform that sequences the 3′- or 5′-end of mRNA and does not allow the identification of splicing QTLs for isoform detection or deep intronic QTLs. These issues can be addressed by the full-length sequencing approaches such as SMART-seq [ 15 ] which, however, comes with a higher cost per cells. High technical noise arising from ribosomal or mitochondrial contamination is another challenge in scRNA-seq data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…eQTL analysis using scRNA-seq is a relatively new approach and only a dozen studies are available [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. These studies show diverse applications of scRNA-seq in identification of the quantitative effects of genetic variants or loci using purified cell types [ 4 , 5 ], induced pluripotent stem cells (iPSCs) [ 6 , 9 , 11 , 13 ] or whole organisms [ 10 ] and to study population ancestry and cell type specific response to an environmental stimulus such as viral infection [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, multiple studies have leveraged scRNA-seq technologies to map cell-type-specific eQTLs across the different subpopulations comprising complex tissues. Studies in peripheral blood mononuclear cells [119], fibroblasts [78], tumor samples [59], and pluripotent and differentiating cells [15, 23, 42, 78] found several eQTLs that would have been missed in bulk sequencing approaches due to being active in only one or a few cell types. While in many single-cell studies most of the detected eQTLs were only found in a single cell type [44, 56, 78], this likely overestimates the overall cell-type specificity of genetic effects on gene expression due to incomplete power of eQTL discovery in these datasets [81].…”
Section: Introductionmentioning
confidence: 99%